Time series analysis of the impact of an intervention in Tayside, Scotland to reduce primary care broad-spectrum antimicrobial use. (7th May 2015) - Hernandez-Santiago, Virginia; Marwick, Charis A.; Patton, Andrea; Davey, Peter G.; Donnan, Peter T.; Guthrie, Bruce
Abstract : Prescribing antimicrobials associated with Clostridium difficile infection in a primary care setting was reduced by substituting antimicrobials as recommended in a guideline rather than by avoiding their use altogether. Further study is necessary to assess the impact on antimicrobial resistance. Abstract: Objectives: Concern about Clostridium difficile infection (CDI) and resistance has driven interventions internationally to reduce broad-spectrum antimicrobial use. An intervention combining guidelines, education and feedback was implemented in Tayside, Scotland in 2009 aiming to reduce primary care prescribing of co-amoxiclav, cephalosporins, fluoroquinolones and clindamycin ('4C antimicrobials'). Our aim was to assess the impact of this real-world intervention on antimicrobial prescribing rates. Methods: We used interrupted time series with segmented regression analysis to examine associations between the intervention and changes in antimicrobial prescribing (quarterly rates of patients exposed to 4C antimicrobials, non-4C antimicrobials and any antimicrobial in 2005–12). Results: The intervention was associated with a highly significant and sustained decrease in 4C antimicrobial prescribing, by 33.5% (95% CI –26.1 to –40.9), 42.2% (95% CI –34.2 to –50.2) and 55.5% (95% CI –45.9 to –65.1) at 6, 12 and 24 months after intervention, respectively. The effect was seen across all age groups, with the largest reductions in people aged 65 years and over (58.4% reduction at 24 months, 95% CI –46.7 to –70.1) and care home residents (65.6% reduction at 24 months, 95% CI –51.8 to –79.4). There were balancing increases in doxycycline, nitrofurantoin and trimethoprim prescribing as well as a reduction in macrolide prescribing. Total antimicrobial exposure did not change. Conclusions: A real-world intervention to reduce primary care prescribing of antimicrobials associated with CDI led to large, sustained reductions in the targeted prescribing, largely due to substitution with guideline-recommended antimicrobials rather than by avoiding antimicrobial use altogether. Further research is needed to examine the impact on antimicrobial resistance.